Analisis Disiplin Kerja Dalam Meningkatkan Kinerja Karyawan PT. Tunas Lima Warna - Naufal Musyafa; Noto Susanto (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This thesis focuses on the analysis of work discipline in improving employee performance at PT Tunas Lima Warna. The main aim of this research is to evaluate the extent to which work discipline influences employee performance. The research methodology involves collecting data through surveys and interviews with employees at PT Tunas Lima Warna. The research results show that work discipline has a significant influence on improving employee performance. Factors such as compliance with company regulations, punctuality, and responsibility are important components in improving employee performance. The implication of this research is the importance of paying attention to developing employee work discipline as an effort to improve the quality of performance which ultimately achieves company goals effectively and efficiently. PT Tunas Lima Warna management can implement training and coaching programs to improve employee work discipline. Apart from that, companies also employees who show good work discipline. This research provides a significant contribution to understanding the importance of work discipline in improving employee performance. It is hoped that the results of this research can become a basis for companies in developing effective and efficient human resource management strategies to achieve organizational goals. The conclusion of this research shows that work discipline is an important factor that needs to be improved to improve employee performance. This research suggests PT Tunas Lima Warna to continue implementing and strengthening work discipline policies to achieve increased employee performance.